Acquiring Resistance Against a Retroviral Infection via CRISPR/Cas9 Targeted Genome Editing in a Commercial Chicken Line - Hellmich, Romina; Sid, Hicham; Lengyel, Kamila; Flisikowski, Krzysztof; Schlickenrieder, Antonina; Bartsch, Denise; Thoma, Theresa; Bertzbach, Luca D.; Kaufer, Benedikt B.; Nair, Venugopal; Preisinger, Rudolf; Schusser, Benjamin (Frontiers in Genome Editing, 2020)
Genome editing technology provides new possibilities for animal breeding and aid in understanding host-pathogen interactions. In poultry, retroviruses display one of the most difficult pathogens to control by conventional strategies such as vaccinations. Avian leukosis virus subgroup J (ALV-J) is an oncogenic, immunosuppressive retrovirus that causes myeloid leukosis and other tumors in chickens. Severe economic losses caused by ALV-J remain an unsolved problem in many parts of the world due to inefficient eradication strategies and lack of effective vaccines. ALV-J attachment and entry are mediated through the specific receptor, chicken Na+/H+ exchanger type 1 (chNHE1). The non-conserved amino acid tryptophan 38 (W38) in chNHE1 is crucial for virus entry, making it a favorable target for the introduction of disease resistance. In this study, we obtained ALV-J-resistance in a commercial chicken line by precise deletion of chNHE1 W38, utilizing the CRISPR/Cas9-system in combination with homology directed repair. The genetic modification completely protected cells from infection with a subgroup J retrovirus. W38 deletion did neither have a negative effect on the development nor on the general health condition of the gene edited chickens. Overall, the generation of ALV-J-resistant birds by precise gene editing demonstrates the immense potential of this approach as an alternative disease control strategy in poultry.